PSV-16 Influence of the late gestation maternal rumen microbiome on the calf meconium and early rumen microbiome. (30th November 2020) - Woodruff, Kelly; Hummel, Gwendolynn; Austin, Kathleen; Smith, Travis; Cunningham-Hollinger, Hannah
Abstract: Understanding the development of the calf rumen microbiome is important in developing manipulation strategies to improve efficiency as the animal ages. We hypothesized that the cow maternal microbiome would influence the colonization of the calf rumen microbiome. Our objective was to relate the microbiomes of the cow rumen fluid (RFC) to the calf meconium (M) and calf rumen fluid (RFN) at twenty-eight days of age. Mature, multiparous Angus crossbred cows (n = 10) from the University of Wyoming beef herd were used in this study. Rumen fluid was collected from the cows prior to parturition. Immediately following parturition, meconium was collected from the calf and at 28 days post-parturition, rumen fluid was collected from the calves. Microbial DNA was isolated using a lysis buffer and mechanical bead-beating procedure and purified using the QIAamp DNA Stool Mini Kit (Qiagen). Amplicon sequencing of the 16S rRNA V4 region was completed on the MiSeq and analyzed with QIIME2. Both alpha and beta diversity were evaluated by sample type and day. Richness and evenness differed by sample type. The greatest richness and evenness was in RFC (q < 0.01) followed by RFN and M, which did not differ from each other (q ³ 0.5). Bray-Curtis and Jaccard beta diversity differed by each sample type (q < 0.01). These data indicate that the M and RFN do not differ in number and distribution of features, but the samples are compositionally different. Additionally, the RFC differed in both alpha and beta diversity from both calf samples. These profiles can be used to develop hypotheses for the pathway of colonization in the early gut yet still reflect the vast differences in the developmental stage between the cow rumen microbiome and the early calf gastrointestinal microbiome.